A Convenient Late-Stage Fluorination of Pyridylic C−H Bonds with N-Fluorobenzenesulfonimide - Meanwell, Michael; Nodwell, Matthew B.; Martin, Rainer E.; Britton, Robert (Angewandte Chemie International Edition, 2016)
Pyridine features prominently in pharmaceuticals and drug leads, and methods to selectively manipulate pyridine basicity or metabolic stability are highly sought after. A robust, metal‐free direct fluorination of unactivated pyridylic C−H bonds was developed. This convenient reaction shows high functional‐group tolerance and offers complimentary selectivity to existing C−H fluorination strategies. Importantly, this late‐stage pyridylic C−H fluorination provides opportunities to rationally modulate the basicity, lipophilicity, and metabolic stability of alkylpyridine drugs. Fashionably late: A robust, metal‐free direct fluorination of unactivated pyridylic C−H bonds was developed. This convenient reaction shows high functional‐group tolerance and offers complementary selectivity to existing C−H fluorination strategies. Importantly, this late‐stage pyridylic C−H fluorination provides opportunities to rationally modulate the basicity, lipophilicity, and metabolic stability of alkylpyridine drugs.